Serious fruit pests controlled - biologicaly - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Several important pests that attack fruit in the South Pacific region are being controlled with biological agents instead of chemical sprays. In some cases this will mean that fruit exports, previously banned because of chemical residues, can soon...